The Burden of Invasive Staphylococcus aureus, Carbapenem-Resistant Gram-Negative Bacilli and Clostridium difficile Infections in Nursing Homes in Monroe County, NY. (4th October 2017) - Hatwar, Trupti; Tsay, Rebecca; Concannon, Cathleen; Gellert, Anita; Nelson, Deborah; Dumyati, Ghinwa; Felsen, Christina B
Abstract: Background: Nursing home (NH) residents are commonly colonized by Staphylococcus aureus, multidrug-resistant Gram-negative bacilli and Clostridium difficile, but the incidence of infection caused by these organisms is not well-described. We quantified the burden of these infections in local NH and the time to infection post-hospital discharge, using surveillance data from the Centers for Disease Control and Prevention's Emerging Infections Program. Methods: In 2016, surveillance for invasive methicillin-resistant and sensitive S . A ureus (MRSA/MSSA), carbapenem-resistant Enterobacteriaceae (CRE), and C. difficile infections (CDI) was performed in 34 NH (bed size range: 28–566) in Monroe County, New York. Incident cases were defined as positive specimens collected in the NH or ≤ 3 days after hospital admission from an NH. Surveillance was limited to sterile sites for MRSA/MSSA; CRE included sterile sites and urine. NH bed census data were used to calculate incidence. Results: A total of 205 cases in 193 persons were identified in 29 NH. CDI was most common with 156 (76%) cases identified; followed by MRSA (24, 12%), MSSA (17, 8%) and CRE (8, 4%). Cases were mainly female (61%) and White (80%) with a mean Charlson score of 5 (SD = 3). CDI cases were older with a median age of 81 years ( P = 0.0007). Twenty-seven (79%) of the NH had a least one case of CDI; 11 (32%) MRSA; 10 (29%) MSSA; and 7 (12%) CRE. Three (9%) NH had at least one case of all organisms. Incidence (per 100, 000 resident days) pooled across NH ranged from 2.4 to 33.3, with incidence differing from expected in 5 (15%) NH (Figure 1). Incidence by NH was highest for CDI: range 2.4–23.6 (median = 7.7), MRSA: 2.0–5.8 (median = 3.1), MSSA: 1.5-8.3 (median = 2.4) and CRE: 0.6–3.8 (median = 2.0). Forty-eight percent of cases developed within 30 days of hospital discharge (median = 13 days (25%-75% IQR = 12)). Conclusion: Incidence varied between organisms and NH; several NH had higher than expected rates of infection. Additionally, 48% of cases were detected shortly after hospital transfer to the NH. These findings highlight possible predictors of infection and prevention targets at both the nursing home and patient-level. Further analysis adjusting for NH characteristics including case mix index and number of transfers from the hospital is needed. Disclosures: R. Tsay, CDC: Independent Contractor, Grant recipient